Idiomatic Translation in The Movie “Spider-Man: Across The Spider-Verse” - Ramawan, Gilang; Ni Luh Putu Krisnawati; I Made Netra (International Journal of Linguistics and Discourse Analytics, 2025)
The study will determine the idioms employed in the movie and the means applied in order to translate them to the target language. The qualitative descriptive approach was used, which was supported by the use of the content analysis to interpret the meaning and role of idioms in the dialogues in the film. Data collection was made through the purposive approach which entailed identifying English conversations having idiomatic expressions and their respective Indonesian subtitles such that only applicable and contextually rich ones were selected and analyzed. This work follows the structure of Fernando (1996), who divides idioms into pure, semi-, and literal idioms in terms of their figurativeness and Baker (2018), who describes four major strategies of translating idioms which are using idioms of similar meaning and the same form, using idioms of similar meaning and different form, paraphrasing, and omission. The results indicate that pure idioms were the most frequent then literal and semi-idioms. Paraphrasing was the translation strategy that prevailed the most and this shows that translators would focus more on meaning and naturalness than literal structure. This is an indication that effective translation of idiomatic language necessitates the ability to be sensitive to both language and culture to maintain the intended tonality and emotional impact in audiovisual media.